2017
DOI: 10.15403/jgld.2014.1121.261.ely
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Supplementation in Patients with Non-Alcoholic Fatty Liver Disease: Systematic Review and Meta-analysis

Abstract: Background: Resveratrol is a potential treatment option for management of non-alcoholic fatty liver disease (NAFLD) due to its anti-inflammatory, antioxidant properties, and calorie restriction-like effects. We aimed to synthesise evidence from published randomized clinical trials (RCTs) about the efficacy of resveratrol in the management of NAFLD.Methods: A computer literature search of PubMed, Scopus, Web of Science, and Cochrane Central was conducted using relevant keywords. Records were screened for eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 18 publications
6
52
2
1
Order By: Relevance
“…Resveratrol (3,5,4′-trihydroxy-trans-stilbene, C14H12O3, molar mass: 228.25 g/mol) is a non-flavonoid phenol ( Figure 9 ) particularly concentrated in the grape skin peel, but also in the extracts of Polygonum cuspidatum , poorly orally bioavailable (if not chemically modified), characterized by an important antioxidant, vasoprotective (both cerebral and peripheral) and insulin-sensitizing activity [ 73 , 74 ]. Preliminary clinical data appear to contradict preclinical literature, suggesting a potential efficacy of resveratrol in improving NAFLD-related parameters [ 75 ]. However, these studies are usually short (too short to have an impact on the liver structure) and are conducted with resveratrol doses incompatible with the insulin-sensitizing action that could improve NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…Resveratrol (3,5,4′-trihydroxy-trans-stilbene, C14H12O3, molar mass: 228.25 g/mol) is a non-flavonoid phenol ( Figure 9 ) particularly concentrated in the grape skin peel, but also in the extracts of Polygonum cuspidatum , poorly orally bioavailable (if not chemically modified), characterized by an important antioxidant, vasoprotective (both cerebral and peripheral) and insulin-sensitizing activity [ 73 , 74 ]. Preliminary clinical data appear to contradict preclinical literature, suggesting a potential efficacy of resveratrol in improving NAFLD-related parameters [ 75 ]. However, these studies are usually short (too short to have an impact on the liver structure) and are conducted with resveratrol doses incompatible with the insulin-sensitizing action that could improve NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of 283 subjects with type 2 diabetes reported that high-dose resveratrol (≥100 mg/day) supplementation improved the fasting plasma glucose level [ 38 ]. Nevertheless, other reports of meta-analysis fail to show the beneficial effects of resveratrol on lipid profile ( n = 763 subjects) [ 39 ] and NAFLD ( n = 158 subjects) [ 40 ].…”
Section: Health Benefits Of Resveratrol Against Metabolic Syndromementioning
confidence: 99%
“…In contrast to these encouraging studies, another very recent, randomized, clinical trial from Denmark including 28 patients with overweight found no indication that RES treatment (1.5 g RES/day for 6 months) had any consistent therapeutic effects (63). In line, a recent systematic review and meta-analysis study published during the revision of the current review concluded that the current evidence was insufficient to support the efficacy of resveratrol in the management of NAFLD (64). A detailed search in the Clinicaltrials.gov registry for clinical RES trials led to the identification of 13 clinical trials when using the search terms "resveratrol" and "liver".…”
Section: Res As a Therapeutically Effective Drug In Human Liver Diseasementioning
confidence: 56%